KEPUASAN KONSUMEN TERHADAP PRODUK KERIPIK CABE DI KELURAHAN SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Syarief Hidayat; Said Suhil Achmad; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The formulation of the problem in this research is how high the consumer satisfaction of chili chips product in Sedinginan Village, Tanah Putih Sub-district, Rokan Hilir Regency? How big is the contribution of consumer satisfaction to chili chips products based on the indicators used as a factor in the Village Sedinginan Tanah Putih District Rokan Hilir Regency? The benefits of this research is to contribute thoughts to the concept of customer satisfaction in urban Sedinginan. This research is descriptive with quantitative approach. The population in this study is 65 people. Sampling in this study using simple random sampling. The instrument used is a questionnaire containing 53 statement items. Consumer Satisfaction Of Chilli Chips Products In Kelurahan Sedinginan Tanah Putih Subdistrict Rokan Hilir Regency is measured by indicators (1) attitude, (2) feeling and (3) expectation. From the results of the study note that Consumer Satisfaction Against Chips Chili Products In Subdistrict Sedinginan Tanah Putih District Rokan Hilir Regency included in the high category. The highest mean on the expectation of consumer satisfaction with mean 3,98 and SD 0,91 then followed by attitude of consumer satisfaction with mean 3,89 and SD 1.00 and after that consumer satisfaction which is low is consumer feeling satisfaction that is mean 3, 87 and SD 0.99. Its meaning is the feeling is not very influential on consumer satisfaction chili chips.Keywords: Consumer Satisfaction Against Product